2015
DOI: 10.5817/cp2015-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Beauty in the eye of the beholder? Attractiveness in a virtual world

Abstract: The current study examines whether traditional offline gender biases regarding physical attractiveness and status transfer to Second Life (SL), a virtual world where residents can easily manipulate the appearance and status of avatars (i.e., graphical representations of the self). Participants (N = 312, 60.58% female, Mage = 29.77, SD = 10.53) reported on demographics, SL usage, and rated the attractiveness of female and male avatars manipulated along physical attractiveness (high vs. low) and status (high vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(122 reference statements)
0
2
0
Order By: Relevance
“…Nonetheless, the present study would provide a useful empirical contribution to the literature in that this is first to show that merely observing another’s subtle body motions produced perceived positive attitudes on the head of actors even in CG characters. Given that artificial faces have been implemented in various circumstances, such as input interface and video instruction materials, and some studies have found that the principles regarding person perception from physical appearance are consistent across virtual and real world conditions (e.g., Guan, Subrahmanyam, Linares, & Cheng, 2015), systematic investigations of the effect of body motion on the formation of impressions of those figures have not been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the present study would provide a useful empirical contribution to the literature in that this is first to show that merely observing another’s subtle body motions produced perceived positive attitudes on the head of actors even in CG characters. Given that artificial faces have been implemented in various circumstances, such as input interface and video instruction materials, and some studies have found that the principles regarding person perception from physical appearance are consistent across virtual and real world conditions (e.g., Guan, Subrahmanyam, Linares, & Cheng, 2015), systematic investigations of the effect of body motion on the formation of impressions of those figures have not been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Online forums and social media have aggravated people's concern with appearance and greatly affected social and consumption behaviors (Grabe, Ward, and Hyde 2008). The advantages of anonymity and lack of immediate social censoring may make such biases more prevalent online (Guan et al 2015). Online transaction platforms (e.g., Uber, Airbnb) typically require sellers to upload real photos as their profile pictures and to display them in prominent positions.…”
Section: Online Profile Picturesmentioning
confidence: 99%